Study of Annealing Conditions on Particle Size of Nickel Ferrite Nanoparticles Synthesized by Wet Chemical Route - Din, I.U. (Taylor and Francis Inc., 2016)
Wet chemical method has been employed for syntheses of nickel ferrite nanoparticles by using nitrate salts of iron and nickel as starting materials. Synthesized product was characterized in terms of thermal stability (TGA), phase determination (XRD) and structure elucidation (FT-IR). Thermal stability of the product was confirmed by TGA studies. Particle size was investigated as a reference of degree and duration of annealing temperature. A linear relationship was observed for size variation of the nickel ferrite nanoparticles with degree of annealing temperature, while size of nanoparticles remains almost constant for different time interval of duration of the annealing temperature. Â© 2016 Copyright Â© Taylor & Francis Group, LLC.